Identifikasi karakteristik morfologi, sistem budidaya, dan pemanfaatan ubi jalar (Ipomoea batatas L.) oleh masyarakat lokal di Distrik Wanggar Kabupaten Nabire - Nursin Leurima; Nouke Lenda Mawikere; Irnanda A.F. Djunna; Saraswati Prabawardani; Alce I. Noya (Cassowary, 2023)
ABSTRACT: Sweet potato (Ipomoea batatas L.) is one of the world's most important food crops with great potential to be developed in Indonesia. This plant is rich in carotenoids and anthocyanins. Anthocyanin compounds in sweet potatoes function as components of healthy food. The purpose of this study was to identify the morphological diversity of sweet potato accessions, cultivation systems, and utilization of local communities in Wanggar District, Nabire Regency. The method used in this research is descriptive method with direct observation techniques in the field, at 3 villages: namely Wiraska, Wanggar Sari, and Karadiri in the Wanggar District, Nabire Regency. Data on sweet potato diversity were analyzed using cluster analysis with the NTSYS version 2.0 program. The result of this research are: (1) At the research sites in the villages of Wanggar Sari, Wiraska, and Karadiri there were 6 cultivars of sweet potato plants based on local names, namely: Unggu, Mokupudugu, Ueta, Mokupudugu, Nota, and Gelakue genotypes. These 6 cultivars had a diversity of morphological characters, (2) Based on the results of the cluster analysis, there are 2 main clusters that have the lowest similarity in morphological characters (34%), namely Cluster I (Unggu and Gelakue) and Cluster II (Makupudugu, Nota, Ueta, Kilumbi). The genotypes of Ungu and Gelakue in Cluster I have similar morphological characters of 43%, (3) Local communities in the Wanggar District still use traditional sweet potato cultivation systems and techniques that have been used from generation to generation, from land clearing to harvesting, and (4) In addition to being used as food, the plant parts of sweet potatoes are also used based on local wisdom communities as traditional medicines and natural fertilizers.